Winds and cloud morphology in the southern polar region of Venus - Luz, David (2010)
Spinning on average 60 times faster than the surface, the atmosphere of Venus is superrotational, a state in which the averaged angular momentum is much greater than that corresponding to co-rotation with the solid globe. The rapid mean flow, which is main- tained by momentum transports in the deep atmo- sphere, presents a puzzle to the atmospheric and plan- etary sciences[1]. After previous missions revealed a bright polar feature at the north pole[9, 10], the Venus Express spacecraft discovered a fast-rotating counter- part at the southern polar region[6], which has been identified as a vortex[2]. The southern polar vortex can be observed at 5.0 μm as a bright, highly vari- able structure which is ∼ 15 K warmer than the sur- rounding air[6]. Although the Venus superrotation has been measured by tracking cloud features at UV and infrared wavelengths[7, 4, 8, 5], the winds in the po- lar region remain poorly constrained. Characterizing the zonal and meridional circulation in this region, as well as their variability, is crucial for understanding the mechanisms that maintain superrotation. In partic- ular, mean zonal winds are necessary to understand the nature of the polar vortex, how it is connected with the general circulation of the atmosphere, and to diagnose momentum transports. Winds at 45 and 65 km can be detected from cloud motion monitoring by the VIRTIS-M subsection on- board the Venus Express (VEX) spacecraft. Our ob- jective is to provide direct wind measurements at cloud tops and in the lower cloud level, in order to help in- terpret the VEX observations concerning the meso- spheric wind regime and temperature fields. In par- ticular, we present direct measurements of the zonal and meridional winds at both altitudes. For this work we selected nadir-pointing, high- spatial resolution VIRTIS data cubes obtained from apocenter in order to minimize the geometric distortion of the polar region. On average these contain lat- itudes extending from the pole to 70S. Since the VIR- TIS field of view is rectangular, lower latitudes are also present but cannot be observed over full latitude circles. Cloud tracking has been performed using the method of digital correlation described in a previous article[3]. VEX orbits were selected so as to have in each one at least one pair of images suitable for track- ing, i.e., with a considerable spatial overlap. Tracking has been performed on pairs of monochromatic im- ages at wavelengths of 1.74 μm, 2.3 μm, 3.93 μm and 5 μm. In the data cubes obtained with longer integration times (3s) the long-wavelength range of the spectrum, above 4.3 μm, is saturated. In those cases we se- lected the 3.93 μm radiance map instead of the one at 5 μm. The monochromatic radiance maps are first ex- tracted from data cubes that have undergone the stan- dard VIRTIS calibration procedures. The maps are then projected onto a polar stereographic grid and the wind retrieval procedure is applied. A total of 20 lat- itude bins, separated by 1 degree were used. For the analysis of transient motions the spatial averaging was done in 72 longitude bins at 5 degree intervals. In order to evaluate the variability over the time scale of one orbit, we have computed the orbital aver- ages, i.e., averages of all measurements coming from one given orbit. These orbital averages are only ap- proximations to temporal averages, since they do not cover one full rotation. The differences between same- orbit averages are apparent in both day and night side averages. Some notable features indicating different day and night side regimes are also apparent in the or- bit averages, and the boundary of the cold collar ap- pears to be a transition latitude. Moreover, the vari- ability that can be observed from orbit to orbit and be- tween series of observations from the same orbit indi- cates that departures from this mean flow are large and a persistent feature of the global circulation.